Economic analysis of the cultivation and production of the cotton crop (Gossypium hirsutum L.) in Al-Hasakah Governorate (Damascus University Journal of agriculture sciences, 2026)
The research aimed to conduct an economic analysis of the cultivation and production of the cotton crop in Al-Hasakah Governorate. The data was collected from a random sample of cotton farmers, the size of which was (268) farmers. Frequencies and percentages were used in addition to calculating some economic and productivity indicators for this crop. The results showed that the average yield was (400) kg / dunum. The total costs of cotton production amounted to (984678.37) SP / dunum, and the value of the total variable costs of the cotton crop was (373957.5) SP / dunum, while the value of fixed costs amounted to (610720.87) SP / dunum, and accordingly the economic profit is estimated at (1090321.63) SP / dunum. As for the economic efficiency, it was (2.11), and the commercial efficiency was (5.55).
Keywords: Cotton Crop; Economic Analysis; Productivity; Al-Hasakah Governorate; Economic Efficiency